2022
DOI: 10.1097/01.aoa.0000853488.23383.09
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Pregnancy Outcomes Attributable to Socioeconomic and Ethnic Inequalities in England: A National Cohort Study

Abstract: (Lancet. 2021;398:1905–1912) Pregnancy outcomes (eg, stillbirth, preterm birth, and neonatal and infant mortality) in high-income countries tend to be worse among patients from ethnic minority groups and lower socioeconomic status (SES) compared with White patients or patients of higher SES. While there are efforts to reduce these inequalities, more information is needed to understand which groups are most affected and how severe these gaps are. This national cohort study examined the socioeconomic and ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, we did not have data about screening for fetal growth restriction, fetal monitoring or one‐on‐one continuous care from a primary midwife through pregnancy and birth. Therefore, residual confounding cannot be fully excluded, despite adjustments for the most important maternal risk factors 18,22 . However, residual confounding does not explain our findings because both the rates of interventions and the rates of adverse perinatal outcomes are likely to be higher in women with an increased risk profile.…”
Section: Discussionmentioning
confidence: 89%
“…For example, we did not have data about screening for fetal growth restriction, fetal monitoring or one‐on‐one continuous care from a primary midwife through pregnancy and birth. Therefore, residual confounding cannot be fully excluded, despite adjustments for the most important maternal risk factors 18,22 . However, residual confounding does not explain our findings because both the rates of interventions and the rates of adverse perinatal outcomes are likely to be higher in women with an increased risk profile.…”
Section: Discussionmentioning
confidence: 89%
“…13 In comparison to non-Hispanic White women, non-Hispanic Black pregnant women with pregestational diabetes may be more challenged to achieve glycemic control due to social determinants of health, including lack of access to quality health care, reduced ability to engage in lifestyle changes, and fewer resources (food, housing, and transportation), in addition to concurrent comorbidities. [14][15][16][17] Many of these social determinants of health are rooted in historical discrimination and systemic racism. 18 Outside of pregnancy, studies have demonstrated that non-Hispanic Black adults with diabetes have worse glycemic control compared with non-Hispanic White individuals.…”
mentioning
confidence: 99%
“…1 Current research, clinical guidance, and global health politics all point to an inadequate response to injustice on the part of SRMN care systems. Consider, for instance, four examples of ongoing injustices globally: the lack of workforce to meet SRMN, 2 the lack of access to safe abortion, 3 the "ethnic", "racial", and socioeconomic disparities present in maternal and newborn outcomes during the Covid-19 pandemic, 4,5 and the severity and persistence of obstetric violence and obstetric racism. 6 Midwifery is often suggested as a solution to the SRMN inequalities resulting from systemic injustice.…”
Section: Introducing Critical Midwifery Studiesmentioning
confidence: 99%